Is simultaneous cranioplasty with cerebrospinal fluid shunts implantation as safe as staged procedures? - Zhou, Qian; Shen, Wei; Zhou, Zhiying; Yang, Xiaofeng; Wen, Liang (Frontiers in Neurology, 2022)
Objective: The combination of cranioplasty and ventriculoperitoneal shunt is a therapeutic strategy for patients with hydrocephalus after decompressive craniectomy (DC). However, the efficacies of simultaneous versus staged surgery in reducing postoperative complications have not been conclusively determined. This was a meta-analysis of relevant studies to assess whether simultaneous surgery significantly reduces postoperative complication risks, compared to staged surgery. Methods: We systematically searched PubMed, Embase, Cochrane, Web of science databases for studies (published by 11 May 2022) comparing patients undergoing concurrent and staged cranioplasty and ventriculoperitoneal shunt. Our main endpoints were; overall postoperative complications, postoperative bleeding, postoperative infection and reoperation. We assessed the pooled data using a random effects model to compare complication rates using odds ratios (ORs) and 95% confidence intervals (CIs). Results: Of the 494 identified studies, 12 were included in our analysis (N=651 participants). Compared to staged surgery, concurrent surgery increased the relative risk for overall complications (pooled OR: 2.00; 95% CI: 1.10 to 3.67), however, it did not increase the relative risks for postoperative bleeding, postoperative infection or reoperation. Subgroup analysis revealed that in the Asian population, concurrent surgery increased the relative risks for overall complications (staged versus concurrent group: OR: 2.41, 95% CI: 1.51-3.83, I2=0.0%) and postoperative infections (staged versus concurrent group: OR: 2.35, 95% CI: 1.06-5.21, I2=31.8%). Conclusions: Compared to staged surgery, concurrent surgery increases the overall complication rates. However, differences between the two therapeutic approaches in terms of postoperative bleeding, postoperative infection, or reoperation are insignificant. Simultaneous surgery was associated with increased overall post-operative complications and post-operative infection rates in the Asian population.